Contributos da segurança privada para a segurança interna portuguesa - Rita, Célcio Tavares do Nascimento (2020)
The main objective of this work is to demonstrate the contribution that private security companies give to internal security in Portugal. Security has been one of the topics most discussed in the international arena and one of the major concerns of the States, and Portugal does not escape the rule even though it is indicated as a country with low crime rates. In a world of constant turmoil, marked by many uncertainties, challenges and diffuse threats to world peace, the sense of insecurity is growing day by day among the population, making states increasingly powerless to guarantee the right to freedom, security and guarantees of citizens. In this reality in which we live private security companies, can make a great contribution to public security, without jeopardizing the fundamental rights of citizens. Private security companies have played a prominent role in internal security in Portugal, being an important element in the prevention and deterrence of the phenomenon of crime, being present in several sectors of the country (public and private) as a complement to the public security. Despite the pros and cons on the activities of private companies or their agents, we are aware that they play a key role in ensuring internal security.